Cytological Studies of Irregular Meiotic Behavior on Some Medicinal Plants: in Al-Anbar, Iraq. - Swadi Nasser, Naji (Iraqi Journal of Science, 2023)
The present study on some wild medical taxa has been carried out from the cytological view-points by using iron-acetocarmine squashtechnique.The chromosome numbers of Diplotaxis harra n=13, Eruca sativa n=11, both Carduus pycnocephallus n=29 and Datura stramonium n=10 were the new reports. Avariety of abnormal Chromosomal behaviours including, early & late disjunction, laggards, bridges, stickiness, and disturbed polarity were observed, albite with low frequency. All sorts of chromosomal abnormalities were counted at I &II meiotic stages. The stickiness frequency was slightly higher than others abnormalities in most stages, The highest stickiness numbers were noted in telophase I/II of D. harra (8.88%), C. pycnocephalis (4.25%), and in metaphase I/II of E. sativa (8.68%), D. strumonium (8.29%). The medical plant wild type used as natural genetic resources.